The Psychological Influence of Contextual Teaching and Learning Models on Students' Social Cohesion Attitudes - Syahril, Firman, Khairani (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This research aims to determine the influence of the contextual teaching and learning model on the learning motivation of class XI students at SMK 1 Padang. This research is of the type quantitative approach with a quasi-experimental method with a non-equivalent comparison-group design. The population used in this study were all students of class XI at SMK 1 Padang, consisting of two classes, namely XIA and XIB. Research data collection techniques with simple random sampling. Technical data analysis to test the hypothesis is done by statistical calculations product-moment correlation. The results of hypothesis testing show that there are significant differences between classes that learn using the contextual teaching and learning learning model and classes that learn without the contextual teaching and learning learning model. This obtained r-count of 0.696 > r-table 0.242 with a significance of 0.05 and n = 66 that H0 was rejected. This means that it can be concluded that there is an influence contextual teaching and learning model for understanding the concept of social cohesion for class XI students of SMK 1 Padang.